2018
DOI: 10.18502/kls.v4i5.2576
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Lighting Conditions for Office Workers from the Perspective of Non-visual Effects

Abstract: Optimal lighting conditions for office environments were examined with respect to effects on productivity, alertness, subjective responses, sleep composition, and circadian rhythms of melatonin and body temperature. Participants were 10 healthy male students (mean age: 24.1 ± 1.1). Three lighting conditions were employed: (1) 750 lx and 5000 K, kept constant from 9:00 to 18:00 ( JIS mode); (2) 400 lx and 5000 K, kept constant from 9:00 to 18:00 (SE mode); and (3) 750 lx and 6000 K from 9:00 to 14:00, followed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 11 publications
0
5
0
1
Order By: Relevance
“…Studies of occupant health and well-being in built environments have recently begun to be conducted. It has been demonstrated that light, in addition to air and water quality, has a strong effect on occupant health and well-being in offices, not only from the point of view of subjective comfort, but also in terms of objective aspects or non-visual effects [15, 19, 21, 33].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies of occupant health and well-being in built environments have recently begun to be conducted. It has been demonstrated that light, in addition to air and water quality, has a strong effect on occupant health and well-being in offices, not only from the point of view of subjective comfort, but also in terms of objective aspects or non-visual effects [15, 19, 21, 33].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have focused on the non-visual effects of light [7, 34], with application studies showing its beneficial effects on human health and well-being and how to translate scientific findings into office lighting designs [15, 19, 22, 23]. Non-visual responses include almost all physiological functions affected by photic signals from ipRGCs projected to all major retinorecipient parts of the brain [28, 35].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations